Integrated Service Center as a Media for Child Legal Protection: a Lessons from Sidoarjo, Indonesia - Andreina Nandya Agung Putri (Indonesian Journal of Law and Economics Review, 2018)
Indonesia ensure the welfare all of the citizens, including the protection Violence against women and children is a violation of human rights. The purpose of this research is to know the service procedure, that is given by P2TP2A to child victim of violence in the household and P2TP2A efforts in tackling domestic violence. This research used a sociological yuridistmetode whit analysis data that collected from describing by observation, interview and documentation as well as literature-related literature. Researchers took samples from Sidoarjo P2TP2A and then analyzed. The results of the research conducted it can be known procedure P2TP2A service victims can report to P2TP2A directly, via the hotline as well as public complaints and media directly. Next, P2TP2A in tackling domestic violence carried out some activities include prevention, service, and rehabilitation. The benefits of this study are expected to provide an understanding of solutions related to the implementation of which can be done P2TP2A appropriate in implementing the protection of children who experience KDRT.